Optimization for flood evacuation shelter location-allocation problems with different priority level constraints - Boromrit, Boonyarit; Jamrus, Thitipong (Engineering and Applied Science Research, 2023)
A natural disaster is a major adverse event. Flooding is a common natural disaster that damages the environment and causes economic losses, deaths, and homelessness. In recent years, floods have significantly impacted people in Asia. Although disasters cannot be avoided, we can develop plans to address their associated problems. However, resources for preparation, capital, time, and employees are limited. This paper aims to address the location-allocation problem in humanitarian aid during catastrophes by planning and managing evacuation of victims from flooded areas to safe locations. A mixed-integer programming model is used to determine the number of shelters needed and to assign the victims to appropriate shelters using a facility location and allocation model. The model considers the total population in each affected area, the travel distance, victim’s priority score, shelter’s priority score, shelter’s capacity, fixed cost for transportation, cost for opening the shelter, and staff wages. To approach the real-world issues, we expand some constraints in the mathematical model concerning the priority level of victims and the capacity limit of facilities. An experiment comparing various scenarios at different problem scales was done to gauge the validity of the proposed approach. The outcomes demonstrated the applicability of the suggested strategy.